-9(1+6+6v)=

Simple and best practice solution for -9(1+6+6v)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9(1+6+6v)= equation:


Simplifying
-9(1 + 6 + 6v) = 0

Combine like terms: 1 + 6 = 7
-9(7 + 6v) = 0
(7 * -9 + 6v * -9) = 0
(-63 + -54v) = 0

Solving
-63 + -54v = 0

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '63' to each side of the equation.
-63 + 63 + -54v = 0 + 63

Combine like terms: -63 + 63 = 0
0 + -54v = 0 + 63
-54v = 0 + 63

Combine like terms: 0 + 63 = 63
-54v = 63

Divide each side by '-54'.
v = -1.166666667

Simplifying
v = -1.166666667

See similar equations:

| 100=x+(x+2) | | 4h-4=8 | | 61.94+56.06-x-45=38 | | -3(-2+9v)= | | -16t^2+18t+10=0 | | -7(n-5)-6n=4n+1 | | 6(2x+3)=11x-3-6x | | 2x^2+10y=-7 | | 11b+3=25 | | t^2-16t+64= | | (2z+1)+9=(6z-9) | | 11=1-7x-3x | | 8t^2+9t+5=0 | | 0.26=-2.5(76-4) | | 5n-11=2n+2 | | 7r^2-2r=0 | | n+6n=-14 | | 4x^2-2x^2+1=0 | | 2y+2=3x+2 | | 14=x(3x+19) | | 3+2a=57 | | 2(x+3)+4x-5= | | -13=7x+8 | | -5+11=13x-2-12x | | 7n-6n=n-5 | | 2x-3x-18=-4x+4 | | .25(12+8m)= | | -5600.00+200x=-2800 | | 11[g]-3=-g+141 | | 8y-4-6y+3=0 | | 2(2+3)-(7*2)=3(2-2)-2*2 | | 9x^2+18xy+9y=0 |

Equations solver categories